An exploratory study of maximal heart rate determination in endurance athletes: laboratory testing vs. field based - Ausland, Å.; Kelemen, B.; Seiler, S. (Frontiers in Sports and Active Living, 2026)
Background: Accurate assessment of cardiovascular parameters, including maximal heart rate (HRmax), resting heart rate (RHR), and heart rate reserve (HRR), is important for guiding training prescriptions in endurance athletes. Conventional age-based HRmax prediction formulas, particularly the widely used "220—age" equation, remain common despite substantial individual variation and documented underestimation in trained populations. Self-reported field data—defined as the highest heart rate recorded during maximal training or racing efforts—provide an ecologically valid alternative for examining HRmax in real-world settings.